Att göra samhällsnyttig information mer lättillgänglig: Konceptualisering av ett digitalt hjälpmedel för den som är ny i Sverige - Furustorp, Heidi; Maxstad, Elin (My University, 2020)
This project examine how a tool may be developed to help recent immigrants assimilate governmental information more effectively. The project form part of the non-governmental organization SOS Children’s Villages and their family strengthening project aimed to make recent immigrants more independent and to relieve children from their family responsibilities. SOS Children’s Villages have since 2017 had operations in Hammarkullen, Gothenburg with the aim of helping unaccompanied children and youth establish and grow independent citizens of Sweden through professional mentorship. Alongside the progression of the mentorship program, the children getting their residence permit had their remaining family members starting to arrive to Sweden. With family members arriving the mentorship needed to change to focus more on family-related issues rather than the growth and personal development of the child. This change led to the launch of The Family-Strengthening Project in the fall of 2019 which explore the experiences of the immigrant families from the assimilation process into Swedish society. Together with SOS Children’s Villages there were initial pre-studies held with focus-groups of recent immigrants to gain further insights. Literary studies were made, forms from immigrant youth and parents were analyzed and interviews with recently immigrated individuals and outside experts were conducted. The collected data and insights were then compiled in an KJ-analysis, personas, problem definition and specification of requirements. The pre-study was followed by two phases of conceptualization that consisted of generating of ideas, prototyping and evaluation of generated results. The project has brought to light the common problems of children having to take charge of duties normally signed to parents. Barriers of the Swedish language limit the parent’s abilities and understanding in the Swedish society, and it makes it hard to take care of their parental responsibilities. This has shown to affect both children and their parents in many ways such as the parents feel alienated and experience that they are viewed as legally incompetent. The increasing obligations of the children lead to a transfer of power from parent to child. A difficulty that has been identified is parents having a hard time navigating across the many societal informational platforms. This leads to parents engaging their children to help them. The information on these platforms may be hard for a child to understand and the process of helping the parent quickly becomes very time-consuming. Our conclusion is therefore a digital tool in the form of an application that systemizes useful information from Swedish authorities and adjusts it to better fit the user’s needs. The application is named ”Ny i Sverige-portal” and is built on reliable sources to which the user is redirected. The application has been made using recognized design principles. It operates in different languages and is also adjusted for use by people with reading impairment through the use of different symbols and recital. Our aim with the application is that parents would be able to seek answers for themselves and furthermore increase their own independence and not depend upon the help of their children.